Aplikasi Software 3 Dimensi Inversi Dalam Interpretasi Sebaran Air Tanah - R. R. Wahyuningrum, Budi Legowo, Darsono (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2013)
3-D resistivity inversion study to determine the distribution of water land in the hamlet Platarejo and hamlet Selorejo been calculated using geoelectric dipole- dipole configuration. Through data processing by using software Res2Dinv and software Res3Dinv. The result obtained from the software Res2Dinv the form of two dimensional cross section with colour imaging for each layer. Result Res2dnv processing software is then input into the software so as to provide a color image Res3Dinv deployment in 3 Dimensional subsurface. From the results of the processing that there are 6 (six) layers having difference thicknesses. Processing results showed the depth of 0,00 m to 10,4 m only have one type of layer is sandy silt till which has resistivity values ranging from 5,5 Om to 14,3 Om. At a depth of 10,4 m to 122,9 m was identified as a layer in the from of tuffaceous sandstone, at a depth of 12,9 m to 18,6 m identified as limestones. So that it can be seen that the distribution of surface soil water was found at a depht of 10,4 m and close the second trajectory is at a distance of 30 m to 90 m and a third track at a distance 30 m to 100 m. Keyword: Resistivity, 3 Dimensional, Groundwater, Platarejo.